PERLINDUNGAN HUKUM PEKERJA MIGRAN INDONESIA DI MALAYSIA MELALUI ONE CHANNEL SYSTEM - Fitria, Yenni; Khairani, Khairani (Ensiklopedia Education Review, 2023)
The efforts made by Indonesia to protect PMI in Malaysia are through diplomacy by entering into a bilateral agreement which resulted in an MoU on the One Channel System in an effort to provide legal protection for Indonesian migrant workers. The MoU is an update to the agreement and mechanism for placing domestic sector PMIs working in Malaysia, and stipulates that PMI placements will only be carried out through the One Channel System. The aim of the research carried out by the author is to find out how legal protection for PMI who work abroad can be an effort to realize equal rights and opportunities for workers to obtain decent work and income, and how the One Channel System can be a solution in providing legal protection for Indonesian migrant workers. This type of research uses normative legal research which includes positive law inventory research, research on legal principles research, research on legal systematics and research on the level of synchronization which is examined by conducting legal studies. After conducting research, the author found that the current policy of placing Indonesian migrant workers abroad for Indonesia is seen as still requiring a philosophical approach to legal protection itself by adapting the form of legal protection to the concrete problems experienced by Indonesian migrant workers, in order to be able to realize their rights. and equal opportunities for workers to obtain decent work and income. The presence of the One Channel System as a solution in providing legal protection for Indonesian migrant workers is welcomed by all groups. With the birth of the MoU regarding this system, it is hoped that Indonesian migrant workers will receive maximum protection both before departure, during placement and after returning to their homeland.Keywords: Protection Law, Pekerja Migran, One Channel System